Information quality life cycle in secondary use of EHR data. (February 2021) - Hausvik, Geir Inge; Thapa, Devinder; Munkvold, Bjørn Erik
Highlights: Explored the role of information quality in the secondary use of healthcare data. Applied the IQ Life-cycle model to understand information quality in secondary use. Revealed how interpersonal communication makes information quality dynamic in secondary use. Identified mechanisms that make IQ dynamic in secondary use, such as filtering, integration, and regeneration. Abstract: The paper argues that existing research on information quality (IQ) mainly focuses on the primary use of electronic health record (EHR) data, whereas IQ in secondary use of EHR data needs further deliberation. The current view of IQ in a healthcare context is static. It assumes that once the EHR system generates the information product, individual users may act on the information based on their subjective perception of its quality. However, this view ignores the complexities of secondary use of EHR data, in which users are actively involved in (re)generating and communicating the information product. Thus, IQ does not remain static but keeps on transforming through active engagement and interpersonal communication. To contribute to this debate, we conducted a qualitative case study in a Norwegian healthcare context by employing an IQ life cycle model. In conclusion, we enhanced the existing IQ model by (1) adding interpersonal communication, (2) showing the interrelations of the IQ dimensions, and (3) integrating the mechanisms of the transformation process for IQ in secondary use of EHR data. In doing so, we unfold the dynamics of IQ in the secondary use of EHR data.